Exploring Degree of Awareness about Health Care and Hygienic Practices in Secondary School Students Residing in Semi-urban Areas of Bangladesh (Community Based Medical Journal, 2013)
Corrigendum: On 25/10/2013 the author Dr. Mahmudul Hasan Siddiqui was replaced by Dr. Mahmudul Hasan Siddiqi.This cross-sectional descriptive study evaluated the general health knowledge and practices of hygiene among semi-urban school children in Bangladesh and assessed the extent to which proper knowledge of hygiene was associated with personal hygiene characteristics. The study population was limited within mature students of class VIII and class X, which were randomly selected. The objectives of the study was first to assess the health knowledge acquired and health care practice undertaken by the students and finally to assess needs for improvement so that they could enjoy a better living and quality life. A well written pre-tested questionnaire was supplied to each student under study. Data were collected and analyzed using Computer Excel Program. The result of the study revealed that approximately 59% of students were classified as having little or no idea or knowledge of health. The majority of the respondents (44.95%) considered early going to bed. Only 11.01% respondents mentioned that they liked to go to bed at late hours after 11 pm. Regarding awakening time, 94.92% respondents in favor of get up early in the morning before sunrise, but actually 36(15%) habituated to get up early in the morning before the sun rise and a great number 200(84.74%) were habituated to late rise. A great number of students (78.81%) were in favor of taking home-made foods and majority respondents considered these foods as safe and wholesome. More than 98% respondents admitted that street vender foods were unhygienic and might cause intestinal disturbances, nausea, vomiting and worm infestation. 100% respondents had access to drink tube well water and it was safe and portable according to 84.75% respondents. To mention about access to proper and adequate defecation facilities it was reported that 90.68% students had the habit to use sanitary latrines. A very low percent of respondents (4.24%) used soap for washing of hands after defecation. About 95.76% of students reported that they washed their hands with water only and soaps were seldom used. The findings with respect to oral hygiene practice, 55.08% respondents preferred to brush teeth. A good number of respondents 50.85%, 20.34%, 15.25%, 8.47% and 5.08% used ash, followed by neem stick, tooth paste, Kalo Majon and magic tooth powder respectively. Although 87.29% of respondents never smoked, but it is very undesirable that more than 10% of students developed smoking habit. The present study revealed that 83.00% of respondents were in favor of keeping nails short. Regarding personal cleanliness 14.83% of the students reported not taking bathing regularly. About 83% realized the importance of wearing underwear. Lastly, the students under interview although clearly stressed upon the need of regular exercise which is good for health, but quite a big number of respondents (91.53%) were not inclined to take exercise regularly. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14186 Community Based Medical Journal Vol.2(1) 2013 55-62